No Jim Crow Church : The Origins of South Carolina's Bahá'í Community - Venters, Louis (Book collections on Project MUSE., 2015)
Venters recounts the unlikely emergence of a cohesive interracial fellowship in South Carolina over the course of the twentieth century, as blacks and whites joined the Baha'i faith and rejected the region's religious and social restrictions.